Acute renal failure and tacrolimus after Liver Transplantation - Nacif, Lucas Souto; David, André Ibrahim; Diniz, Marcio Augusto; Crescenzi, Alessandra; Andraus, Wellington; Pinheiro, Rafael Soares; Cruz, Ruy Jorge; D’Albuquerque, Luiz Carneiro (Brazilian Journal of Transplantation, 2013)
Introduction: Liver transplantation (LT) has considerably improved survival in patients with end-stage liver disease. But it remains a challenge to achieve optimal immunosuppressive therapy avoiding early complications and renal failure. Purpose: To evaluate the serum level of tacrolimus with early acute renal failure after liver transplantation in the first 30 days of admission or until discharge. Method: We studied clinical and laboratory data from patients who underwent liver transplantation from October 2011 to February 2013. It was excluded those from living donor, acute hepatitis, split liver, using other immunosuppressants besides routine (tacrolimus and prednisone), those severe ill and who died before 30 days. Statistical analysis was performed using descriptive measurements (mean ± standard error) of variables: tacrolimus serum levels (ng/ml), glomerular filtration rate (GFR) (ml/min) and creatinine (mg/dl). Comparison of variables by analysis of variance (ANOVA) with repeated measures nonparametric statistical program R, version 2.15.1. Statistically significant at p <0.05. Result: We observed a high prevalence of male patients (68.18 %). The average age of patients was 52.43 (±12.33) and median of 55.5 (range , 19-71 years). The mean hospital stay was 16.1 ± 9.32 days. The main cause for liver transplantation was hepatitis C (47.7%). The mean MELD score for patients was 26.18 ±4.28. Graphic analysis over time showed a significant correlation between the tacrolimus serum value, with deterioration of the glomerular filtration and serum creatinine rates. The comparative analysis showed a statistical difference in relation to serum levels of tacrolimus and infection (p=0.076) and with respect to time (p=0.0001). We note that in the studied population 11.37% of the acute cellular rejection cases and 36.37% of the cases of infection. Conclusion: The serum level of tacrolimus when exceeding 10 ng/ml causes a deterioration of renal function rate.